2021
DOI: 10.2355/isijinternational.isijint-2020-623
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Delay and Texture Memory Effect of Columnar Grained Cast Slab in Low Grades Non-oriented Electrical Steels

Abstract: The cast slab of low grades non-oriented electrical steels experiences twice diffusional solid phase transformation and demonstrates the features of strong morphological memory referring to columnar structure and texture memory referring to the preferred < 100 > texture at room temperature. In this paper, electron backscatter diffraction (EBSD), quasi-insitu observation of heating samples, and dilatometry are used to study and analyze the two kinds of memory phenomena. The results show that the cast slab consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The commercial products are subjected only to recrystallization annealing in the third stage. Based on our previous quasi-in situ observation of the coarse columnar grains structure in cast slabs, it is confirmed that many columnar grains are retained δ ferrite and the transformation from δ ferrite to austenite is delayed or even suppressed in low-grade electrical steels, showing morphological and texture memory effects of {100} columnar grain structure [1,7,8]. We then suggest a new way of increasing {100} texture in hot-rolled bands to improve magnetic properties of final products, namely the so-called metastable ferrite hot rolling method [7].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The commercial products are subjected only to recrystallization annealing in the third stage. Based on our previous quasi-in situ observation of the coarse columnar grains structure in cast slabs, it is confirmed that many columnar grains are retained δ ferrite and the transformation from δ ferrite to austenite is delayed or even suppressed in low-grade electrical steels, showing morphological and texture memory effects of {100} columnar grain structure [1,7,8]. We then suggest a new way of increasing {100} texture in hot-rolled bands to improve magnetic properties of final products, namely the so-called metastable ferrite hot rolling method [7].…”
Section: Introductionmentioning
confidence: 78%
“…Based on our previous quasi-in situ observation of the coarse columnar grains structure in cast slabs, it is confirmed that many columnar grains are retained δ ferrite and the transformation from δ ferrite to austenite is delayed or even suppressed in low-grade electrical steels, showing morphological and texture memory effects of {100} columnar grain structure [1,7,8]. We then suggest a new way of increasing {100} texture in hot-rolled bands to improve magnetic properties of final products, namely the so-called metastable ferrite hot rolling method [7]. By making use of this feature of columnar grain structure during transformation, the slabs can be heated quickly to a high temperature of austenite single-phase region, but before pronounced transformation to austenite takes place, hot rolling is conducted on ferrite, thus initial {100} texture can be retained to some extent without the detrimental influence of grain refinement by the transformation to ferrite.…”
Section: Introductionmentioning
confidence: 78%
“…The presence of columnar grain structure at room temperature in the continuous casting slabs of low‐grade electrical steels indicates that the solid phase transformation of austenite to ferrite is significantly suppressed during casting. [ 1 ] Under the conditions of slow cooling of a 230 mm thick continuous casting slab, the coarse columnar grains didn't become fully refined and equiaxed. In commercial production lines, following the high‐temperature holding for 2–3 h, the thick slabs will undergo rough rolling and finish rolling processes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the morphology and texture memory and phase transformation hysteresis phenomena occur after twice phase transformations in cast slab, and 70% of the cast slab consisting of the {100} columnar grains has not experienced phase transformation, which has been confirmed by the quasi‐in situ heating and cooling phase transformation process. [ 3 ] The columnar grains contain many Σ3 grain boundaries and {100} subgrains. [ 3,4 ] Furthermore, many small equiaxed grains have the Σ3 relationships with the surrounding columnar grains or other variants, which indicates that the twice phase transformations follow the K−S relationship.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] The columnar grains contain many Σ3 grain boundaries and {100} subgrains. [ 3,4 ] Furthermore, many small equiaxed grains have the Σ3 relationships with the surrounding columnar grains or other variants, which indicates that the twice phase transformations follow the K−S relationship. It is also observed that the size of the small {100} subgrains is similar to that of the other equiaxed variants, but the formation reason of {100} subgrains has not been reported.…”
Section: Introductionmentioning
confidence: 99%